Geochemical insights and model optimisation for pilot-scale passive treatment of manganese and zinc in a legacy mine in Japan - Sereyroith Tum; Taiki Katayama; Naoyuki Miyata; Miho Watanabe; Yohey Hashimoto; Miu Nishikata; Tetsuo Yasutaka (Heliyon)
Elevated concentrations of manganese (Mn2+) and zinc (Zn2+) in water bodies can disrupt ecosystems and damage aquatic life. However, the mechanisms underlying the removal of Mn2+ and Zn2+ under dynamic conditions and the optimal hydraulic retention time (HRT) for passive treatment plants remain unclear. Here, a pilot-scale passive treatment system for the removal of Mn2+ and Zn2+ from legacy mine drainage in northern Japan is proposed; it was performed at circumneutral pH for 152 days. Comprehensive suspended solid mineralogy analyses and geochemical and numerical modelling were conducted to optimise the passive treatment efficiency. Mn2+ removal (efficiency reaching 98 %) primarily depended on the activity of Mn-oxidising bacteria. Zn2+ removal involved Zn2+ co-precipitation with birnessite combined with adsorption or ion exchange on the birnessite surface. The inverse numerical model successfully determined the Mn2+ oxidation rate constant, Zn mass transfer coefficient, and Zn distribution coefficient. Under dynamic conditions, HRT emerged as a key factor underlying the pilot-scale passive treatment efficiency. An HRT of 0.5 days led to optimal Mn2+ and Zn2+ removal conditions and achieved values lower than the Japanese national effluent limit. The findings provide crucial information for passive treatment strategy development and environmental management, especially when considering real-scale implementation.